2022
DOI: 10.32607/actanaturae.11723
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Pathological Interaction between β-amyloid and Mitochondria in the Occurrence and Development of Alzheimer’s Disease

Abstract: Alzheimers disease (AD) is one of the most common neurodegenerative diseases in existence. It is characterized by an impaired cognitive function that is due to a progressive loss of neurons in the brain. Extracellular -amyloid (A) plaques are the main pathological features of the disease. In addition to abnormal protein aggregation, increased mitochondrial fragmentation, altered expression of the genes involved in mitochondrial biogenesis, disruptions in the ERmitochondria interaction, and mitophagy are observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 232 publications
0
2
0
Order By: Relevance
“…Among the multiple factors that can contribute to ROS production in AD brains, such as neuroinflammation and abnormal metal homeostasis (Fe, Cu and Zn), mitochondria are the major source of ROS generation [98]. It is thought that Aβ oligomers trigger a significant influx of Ca 2+ into the mitochondria, causing membrane depolarization, enhanced ROS production, metabolic dysfunction, and eventually cytochrome C release, initiating apoptosis [99]. The evidence of altered energy and oxygen metabolisms and mitochondrial dysfunction early in AD pathogenesis, before any sign of Aβ or tau pathology, led to the mitochondrial cascade hypothesis proposing that the aggregations of Aβ and tau in AD might be a compensatory response to underlying oxidative stress [100].…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the multiple factors that can contribute to ROS production in AD brains, such as neuroinflammation and abnormal metal homeostasis (Fe, Cu and Zn), mitochondria are the major source of ROS generation [98]. It is thought that Aβ oligomers trigger a significant influx of Ca 2+ into the mitochondria, causing membrane depolarization, enhanced ROS production, metabolic dysfunction, and eventually cytochrome C release, initiating apoptosis [99]. The evidence of altered energy and oxygen metabolisms and mitochondrial dysfunction early in AD pathogenesis, before any sign of Aβ or tau pathology, led to the mitochondrial cascade hypothesis proposing that the aggregations of Aβ and tau in AD might be a compensatory response to underlying oxidative stress [100].…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Consequently, the enhancement of autophagy to remove Aβ, CTFβ and p-tau proteins, preventing cell death, may be a promising therapeutic strategy, especially in the early stages of AD [111,112]. In this context, a study by Zhao et al has convincingly demonstrated that DHA, the active metabolite of artemisinins corrected autophagy dysfunction in the initial stage of Aβ pathology in APPswe/PSEN1dE9 mice and in cell models of AD (N2a-APP and SH-SY5Y-APP) by acting on multiple targets within the autophagic process [99]. Transmission electron microscopy and measurements of autophagy stage-specific proteins have evidenced that DHA treatment not only activates autophagy via the upregulation of ATG5, ATG12, ATG16L and LC3 II/I and decrease in ubiquitin-binding p62 protein levels, but it also promoted the fusion of autophagosomes and lysosomes (increases in Beclin1, ATG14, Rab7 and RILP levels) and, thus, elevated the number of lysosomes and their degradation function.…”
Section: Autophagymentioning
confidence: 99%